Jane Beats Them All: Price Formation and Financial Returns to Investing in Rare Books - Heinrich Ursprung (Center for Economic Studies and Ifo Institute (CESifo), 2020)
I report historical prices and estimate financial returns to investing in rare books. My sample consists of 25 fiction titles recommended by Clifton Fadiman in his 1960 Lifetime Reading Plan. Relying on prices realized at American and British auction houses between 1975 and 2018, I use hedonic regressions to estimate the average rate of return to each of the 25 titles. Jane Austen's novel Pride and Prejudice tops the returns to all other titles. I then construct for the entire sample of rare books price indices based on various specifications with a view to identifying the most efficient way of computing rare book price indices for larger samples of books. Estimating the financial return to investing in rare books in general, I arrive for the boom period 1975-2007 at a real rate of return of about 4.6%, which exceeds similar estimates for investing in fine art. In a comparison with the returns in 1975-2007 of almost 9% from the US stock market, investing in rare books is justified only by substantial nonpecuniary returns.
Keywords: G11; Z11; 330; are books; price indices; investment in collectibles; cultural economics